SIL-IoVTs: A Bi-Level Optimization Approach for Pest Control and Intruder Monitoring in Smart Agriculture - Zhang, Yuhao; Si, Pengju; Shu, Lei (IEEE International Conference on Industrial Technology (Online), 2025)
Solar Insecticidal Lamps Internet of Things (SIL-IoTs), used for green agriculture, face theft and destruction due to high costs. To address this, we introduce SILC nodes by embedding cameras in SIL nodes, forming SIL-IoVTs for pest control and intruder monitoring. SIL-IoVTs involve omni-directional (SIL) and directional (camera) sensing models for area and target coverage. We formulate an optimal deployment model and develop a bi-level algorithm to solve it, iteratively deploying SIL nodes for pest control and cameras for monitoring. Simulation results show the method's effectiveness and progressiveness.